Nguyên lý quản trị theo định hướng trọng dịch vụ, thành quả đổi mới và thành quả kinh doanh của doanh nghiệp - Nguyễn Văn, Tuấn; Lê Nguyễn, Hậu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The emerging perspective of service-dominant logic has recently attracted the interest of scholars worldwide. To bring this theoretical perspective to management practices, however, it is imperative to provide evidence supporting its superiority through its operationalized construct of service- dominant orientation. This study is aimed to investigate the effects of service-dominant orientation on the strategic outcomes of a firm. Based on the analysis of data collected from 379 firms in Vietnam, the results show that: (i) Service-dominant orientation does induce positive business and innovation outcomes of a firm; (ii) service-dominant orientation is applicable in both service providers and manufacturers. Theoretical and managerial implications are discussed accordingly